Vibration modeling of hard disk drive components - Cheng, Tian. (2010)
In this project, modal analysis was conducted to characterize the actuator in terms of dynamics performance. In a typical hard disk drive, the actuator is widely used to read and write data on the platter. Since the actuator has the read/write heads on its tip of very end, and the distance between platter surface and slider head is too narrow, thus it is very important to know at which frequency the actuator will start to sway off the track duo to its vibration during whole system in operation. Actually, position accuracy of actuator head can be control by the servo bandwidth. Higher servo bandwidth will enhance the position accuracy of actuator head. However, servo bandwidth is limit by the resonant frequency of actuator.